Peran Zakat dalam Perekonomian di Indonesia - Teti Arnita (EKOMA : Jurnal Ekonomi, Manajemen, Akuntansi, 2024)
This study aims to analyze the role of zakat in Indonesia's economy, particularly as a strategy for poverty alleviation. Zakat, as one of the instruments in Islamic economics, has significant potential to support economic and social development. Although zakat plays an important role in societal welfare, its realization and management still face various challenges. This study uses a qualitative method with a literature review approach, analyzing literature from various sources related to fiscal policy, zakat, and Islamic economic concepts. Through this research, it is hoped that a deep understanding of the effectiveness of zakat policies and their contribution to poverty alleviation in Indonesia can be obtained. The findings of this study are expected to provide recommendations for improving the optimization of zakat management in Indonesia.